Can Environmental Corporate Social Responsibility Reduce Firms’ Idiosyncratic Risk? Evidence From China - Kong, Xiaoran; Pan, Yuying; Sun, Huaping; Taghizadeh-Hesary, Farhad (Frontiers in Environmental Science, 2020)
Environmental corporate social responsibility (ECSR) can be a strategy to increase the transparency of investment information effectively to alleviate information asymmetry. The purpose of this paper is to examine the impact of ECSR on firms' idiosyncratic risk. Using the data of A-share listed firms in China and data of Rankins CSR Ratings (RKS) by developing econometrics models, this study document that ECSR can significantly reduce the firms' idiosyncratic risk. This result continues to hold after a series of robustness checks. Besides, the results of conditional analyses reveal that the effect of ECSR is more pronounced for state-owned firms and firms with weaker external monitoring mechanisms and low internal control. Moreover, further evidence suggests that firms with high ECSR show a greater tendency to disclose more information, which reduces the information asymmetry and offer linkages from ESCR to firms' idiosyncratic risk.